Chemotherapy for prostate cancer: Clinical practice in Canada - Saad, Fred; Asselah, Jamil (Canadian Urological Association Journal, 2013)
Whereas prostate cancer was once deemed unresponsive to chemotherapy, there is now evidence that patients with metastatic castration-resistant prostate cancer can obtain a survival benefit from both first-line (docetaxel-based) and second-line (cabazitaxelbased) chemotherapy. The side effects of these agents have been shown to be predictable and manageable, particularly in North American centres. However, patient selection remains a key issue, with the aim of delivering each line of treatment at a time when the individual patient remains fit and well enough to tolerate acytotoxic regimen. Hence, it is increasingly important for urologists and oncologists to work together to ensure timely consideration ofthe chemotherapeutic approach before it is precluded by a decline in performance status.